Proceedings of the Conference on Human Factors in Computing Systems - CHI '03 2003
DOI: 10.1145/642655.642656
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive strategies and eye movements for searching hierarchical computer displays

Abstract: This research investigates the cognitive strategies and eye movements that people use to search for a known item in a hierarchical computer display. Computational cognitive models were built to simulate the visual-perceptual and oculomotor processing required to search hierarchical and nonhierarchical displays. Eye movement data were collected and compared on over a dozen measures with the a priori predictions of the models. Though it is well accepted that hierarchical layouts are easier to search than nonhier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 6 publications
1
36
0
Order By: Relevance
“…Thus, they have been widely used in studies on cognitive modeling especially on cognitive tasks related to visual objects shown on computer displays [14]. Some researchers also used eye trackers to help validate and compare cognitive models of visual search tasks [7,12,15,25]. There is also research about using eye trackers to better understand human users' cognitive processes when interacting with security-sensitive systems, e.g., recently Miyamoto et al [22] conducted a study on using eye-tracking data to link UI elements to the detection of possible phishing websites.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, they have been widely used in studies on cognitive modeling especially on cognitive tasks related to visual objects shown on computer displays [14]. Some researchers also used eye trackers to help validate and compare cognitive models of visual search tasks [7,12,15,25]. There is also research about using eye trackers to better understand human users' cognitive processes when interacting with security-sensitive systems, e.g., recently Miyamoto et al [22] conducted a study on using eye-tracking data to link UI elements to the detection of possible phishing websites.…”
Section: Related Workmentioning
confidence: 99%
“…Alsharnouby et al [3] used eye trackers to assess the influence of browser security indicators and the awareness of phishing on a user's ability to avoid cyber attacks. While there is quite some work on the combined use of eye tracking and cognitive modeling, to the best of our knowledge, except some general recommendations such as those reported in [15] still limited work has been done on combining the two techniques for cyber security applications. This paper aims to further advance this neglected area.…”
Section: Related Workmentioning
confidence: 99%
“…Generally speaking, in order to model human behavior with the highest possible degree of fidelity, it is important to understand precisely what the eyes are doing. Hornof and Halverson (2003) demonstrated the applicability of eye tracking to cognitive modeling in their analysis of visual search strategies. In this study, eight models were created to simulate performance on a letter search of a static computer interface.…”
Section: Convergent Research On Cognitive Models and Eye Movementsmentioning
confidence: 99%
“…This knowledge enables designers to structure the user interface effectively and influence the user's visual search behaviour. Post-cognitive modelling research, as cited in [17], has demonstrated that people use anticipatory location information to guide visual search, and that visual features sometimes guide the visual search (i.e., expectations and salience) [18]. It is through visual search primarily that users locate the content and control for their web-based tasks.…”
Section: Visual Search Behaviourmentioning
confidence: 99%
“…It is through visual search primarily that users locate the content and control for their web-based tasks. Despite extensive research into visual search behaviour in disciplines such as psychology, recent research in HCI [15,18] has underlined the importance of developing a unified understanding of the visual search in HCI. Visual search behaviour on websites is influenced by expectations about what is being looked for and where it might be located.…”
Section: Visual Search Behaviourmentioning
confidence: 99%